2010
DOI: 10.1530/rep-10-0146
|View full text |Cite
|
Sign up to set email alerts
|

The effect of monosaccharide sugars and pyruvate on the differentiation and metabolism of sheep granulosa cells in vitro

Abstract: The objective of this study was to investigate the effect of three monosaccharides or pyruvate on the ability of gonadotrophins to induce cellular proliferation and differentiation of cultured sheep granulosa cells. Lactate production and levels of mRNA expression for the glucose transporters SLC2A1, SLC2A4, SLC2A5 and SLC2A8 were also determined. No energy source in the culture media reduced cell number (50%) and oestradiol (E 2 ) production. Dose and type of monosaccharide had a highly significant (P!0.001) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 54 publications
2
30
2
Order By: Relevance
“…This condition typically occurs in women with a deficiency in or a mutation on one of the key enzymes required for galactose metabolism, namely galactose-1-phosphate uridyltransferase (GALT). Little is known of the patterns of expression of these enzymes in ruminants, but these toxic effects of galactose are consistent with the observation that high doses of galactose inhibit the FSH-induced differentiation of sheep granulosa cells (Campbell et al 2010b) and ovarian oestradiol and androstenedione secretion following direct ovarian infusion in sheep (Campbell et al 2010a). Despite a theoretical availability of the glycolytic pathway for galactose metabolism, we have found that of the monosaccharide tested, galactose was the least well used by ovine granulosa cells, with very little lactate being synthesised compared with glucose or fructose (Campbell et al 2010b).…”
Section: Introductionmentioning
confidence: 62%
See 4 more Smart Citations
“…This condition typically occurs in women with a deficiency in or a mutation on one of the key enzymes required for galactose metabolism, namely galactose-1-phosphate uridyltransferase (GALT). Little is known of the patterns of expression of these enzymes in ruminants, but these toxic effects of galactose are consistent with the observation that high doses of galactose inhibit the FSH-induced differentiation of sheep granulosa cells (Campbell et al 2010b) and ovarian oestradiol and androstenedione secretion following direct ovarian infusion in sheep (Campbell et al 2010a). Despite a theoretical availability of the glycolytic pathway for galactose metabolism, we have found that of the monosaccharide tested, galactose was the least well used by ovine granulosa cells, with very little lactate being synthesised compared with glucose or fructose (Campbell et al 2010b).…”
Section: Introductionmentioning
confidence: 62%
“…Evidence of glucose transporter expression (SLC2A1 and SLC2A4) on granulosa and theca cells of sheep antral follicles (Williams et al 2001) and ovarian arteriovenous difference studies suggest that glucose is taken up by the ovary in significant amounts (Rabiee et al 1997;Scaramuzzi et al 2010). Furthermore, studies using cultured cells in our laboratory have shown that glucose, metabolised under anoxic conditions to lactate, is the preferred energy substrate to support the gonadotrophin-induced differentiation of ovine granulosa cells (Campbell et al 2010b). …”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations